Effect of light emutting diode (LED) lamps and N-acetylglucosamine (NAG) on organogenesis in protocorm-like bodies (PLBs) of a Cymbidium hybrid cultured in vitro - Kamal, Mohammad Mostafa; Shimasaki, Kazuhiko; Akter, Nasren (Plant Tissue Culture and Biotechnology, 2015)
Abstract not available Plant Tissue Cult. & Biotech. 24(2): 273-277, 2014 (December)